Load testing of bridges : proof load testing and the future of load testing. - Lantsoght, Eva O. L. (Milton : CRC Press LLC, 2019)
Load Testing of Bridges, featuring contributions from almost fifty authors from around the world across two interrelated volumes, deals with the practical aspects, the scientific developments, and the international views on the topic of load testing of bridges. Volume 13, Load Testing of Bridges: Proof Load Testing and the Future of Load Testing, focuses first on proof load testing of bridges. It discusses the specific aspects of proof load testing during the preparation, execution, and post-processing of such a test (Part 1). The second part covers the testing of buildings. The third part discusses novel ideas regarding measurement techniques used for load testing. Methods using non-contact sensors, such as photography- and video-based measurement techniques are discussed. The fourth part discusses load testing in the framework of reliability-based decision-making and in the framework of a bridge management program. The final part of the book summarizes the knowledge presented across the two volumes, as well as the remaining open questions for research, and provides practical recommendations for engineers carrying out load tests. This work will be of interest to researchers and academics in the field of civil/structural engineering, practicing engineers and road authorities worldwide.
OCLC-licensed vendor bibliographic record.
Keywords: Bridges -- Testing; Bridges -- Live loads; Dynamic testing; TECHNOLOGY -- Construction -- General; TECHNOLOGY -- Engineering -- Civil